2007
DOI: 10.1186/1471-2334-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal monitoring of Ehrlichia ruminantium infection in Gambian lambs and kids by pCS20 PCR and MAP1-B ELISA

Abstract: Background: The epidemiology of E. ruminantium infection in extensively managed young animals is not adequately understood. Thus in this study, we monitored the onset (age at first infection) and kinetics of E. ruminantium infection and antibody response in extensively managed newborn lambs and kids at three sites in The Gambia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Different specific PCR assays were used to detect Anaplasmataceae DNA in blood samples from African buffalo in the Gorongosa National Park, Mozambique. All the 97 blood samples tested were negative in a specific nested PCR for E. ruminantium (based on pCS20 gene) [ 16 ] and in a multiplex real-time PCR for E. chaffeensis (based on vlpt gene) and A. phagocytophilum (based on msp2 gene) [ 15 ]. Seventy African buffalo (72.2 %) were shown to be positive for amplification of fragments of the gene msp1 β in the real-time PCR specific for A. marginale .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different specific PCR assays were used to detect Anaplasmataceae DNA in blood samples from African buffalo in the Gorongosa National Park, Mozambique. All the 97 blood samples tested were negative in a specific nested PCR for E. ruminantium (based on pCS20 gene) [ 16 ] and in a multiplex real-time PCR for E. chaffeensis (based on vlpt gene) and A. phagocytophilum (based on msp2 gene) [ 15 ]. Seventy African buffalo (72.2 %) were shown to be positive for amplification of fragments of the gene msp1 β in the real-time PCR specific for A. marginale .…”
Section: Resultsmentioning
confidence: 99%
“…DNA samples were screened by different conventional PCR assays: a nested PCR for E. ruminantium [ 16 ]; two nested PCRs for Anaplasma spp. based on partial sequences of the 16S rRNA gene for detection of A. phagocytophilum , A. bovis and A. platys [ 17 ], and for A. centrale and A. marginale [ 18 ]; a nested PCR for the groEL gene [ 19 – 21 ]; a PCR based on the major surface protein 5 (MSP5) gene [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serological tests for heartwater also exhibit false-negative results, mostly in cattle, as antibody levels are often too low to be detected, even in animals that are under continuous natural challenge by infected ticks (23,24). It has been demonstrated that results from the MAP1B ELISA test do not correlate well with those from a nested pCS20 polymerase chain reaction (PCR) test (25), and it is this latter test that the authors will discuss next.…”
Section: Ante-mortem Diagnosismentioning
confidence: 97%
“…Therefore, to prevent the introduction and spread of Foc races in different new regions of India, a suitable, reliable and rapid detection method is prerequisite. In recent years, PCR-based methods, for instance multiplex and real-time PCR have been developed to detect fungal species and other microorganisms [ 8 - 11 ], however, methods based on PCR can be time-consuming and require the extraction of high-quality DNA due to the effects of inhibitors on PCR sensitivity [ 12 , 13 ]. Loop-mediated isothermal amplification (LAMP) is an alternative amplification technology [ 14 ], is highly sensitive, less time-consuming than conventional PCR-based methods, and less prone to inhibition from DNA preparations [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%